Devastating Ischemic Stroke Following Selective Arterial Embolization of a Large Chest Wall Aneurysmal Bone Cyst. Issue 5 (July 2015) - Beardsley, Andrew L.; Teagarden, Alicia M.; Abu-Sultaneh, Samer; Lutfi, Riad
<x xml:space="preserve">Abstract</x> Aneurysmal bone cysts (ABC) are benign bone lesions found in children and young adults. Rarely, these lesions can arise from ribs, and there is disagreement on the best treatment because of proximity to vital structures. Frequently, surgeons remove ABC with en bloc resection. Selective arterial embolization has been used as an adjunct to surgery, or rarely as the primary treatment. We report a case of embolic stroke complicating embolization of a rib ABC, likely from the presence of collateral circulation between the mass and vertebral artery. Caution should be taken when performing embolization of lesions in this location because of potential complications.